Children's testimony and the emotional victim effect - Landström, Sara (Legal and criminological psychology, 2015)
Purpose Two experiments were conducted to examine the effects of (1) child victims’ emotional expression during testimony and (2) the camera perspective used to record the testimony, on judgements of credibility. Methods Law students (N = 155 in Experiment 1; N = 86 in Experiment 2) watched a child harassment complainant provide a statement in an emotional or neutral manner, presented using different camera perspectives: balanced focus (i.e., a shot portraying an equal focus on the child complainant and the interviewer) versus picture-in-picture (PiP; i.e., a shot portraying only the child with an inset window depicting both the child and the interviewer in the corner of the screen) in Experiment 1 and PiP versus child focus (i.e., a shot depicting only the child) in Experiment 2. Results Although no effect was found for camera perspective, the results provide support for an emotional victim effect (EVE); the child was perceived as more credible and truthful when communicating the statement in an emotional (vs. neutral) manner. Moreover, the results provide corroborating evidence for the assumption that the EVE rests on both cognitive (expectancy confirmation) and affective (compassion) mechanisms. Conclusions These findings extend previous research by showing that the EVE and its underlying mechanisms apply to judgements of child complainants in the context of non-sexual crimes and appear to be robust against variations of camera perspectives. Legal implications are discussed.